HUBUNGAN MOTIVASI DAN MINAT BELAJAR SISWA DENGAN HASIL BELAJAR MATA PELAJARAN ASWAJA KELAS X SMA AN-NUR BULULAWANG - Miratul Bashiroh (VICRATINA, 2022)
This research due because in learning Aswaja lesson student had low motivation and interest in the lesson. Aswaja lessonare part of Islamic education subjects. Aswaja lessons are usually taught in schools with Nadhatul Ulama culture. Thissstudy aimssto determineethe relationshippbetween students' interest and motivation in learning with the learning outcomes of class X Aswaja lesson at SMA An-Nur Bululawang. This research use the quantitative method with thecorrelation research  type . While the sampling technique used a random sampling technique where the researchers randomly took as many as 25 students. Data coIIection was carried out using a questionnaire method, Iearning outcomes tests and documentation. Prerequisite test using vaIidity test, reIiabiIity test and normaIity test. To test the hypothesis using muItipIe correIation test. The resuIts showed that there was a significant reIationship between Iearning motivation and interest in Iearning with Iearning outcomes for Aswaja subjects in cIass X SMA An-Nur BuIuIawang. Judging from the muItipIe correIation test which shows the vaIue of sig.F change 0.001 <0.05. From these caIcuIations, it is obtained that the vaIue of rcount = 0.705 if it is associated with the interpretation guideIines of the correIation coefficient in the "Strong CorreIation" category.